Addressing parent-adolescent roles and interactions to improve adolescents’ diets in Ethiopia - Kim, Sunny S.; Sununtnasuk, Celeste; Vu, Thu Trang; Sanghvi, Tina; Walissa, Tamirat; Nguyen, Phuong Hong (Elsevier, 2024)
Objectives: Adolescence is a critical period of development and habit formation including healthy dietary practices. Nutrition education interventions were implemented in government primary schools in rural Ethiopia. This study examined (1) the impact of interventions on nutrition knowledge, parent-adolescent interactions, and parental food control; and (2) the relationships among knowledge, interaction, and food control on adolescents’ diets. Methods: We used endline survey data from a cluster-randomized program evaluation, among adolescent girls aged 10-14 years (N=536) enrolled across 54 primary schools. Interventions included specialized school-based nutrition education activities, and the control received standard school curriculum. Descriptive statistics were used to assess the differences between program groups. Multivariable regression analysis was used to assess factors associated with diets (dietary diversity, meal frequency, and junk food consumption), adjusting for covariates at adolescent, parental and household levels and school clustering. Structural equation models were used to assess the relationships among the intervention, knowledge, interactions, and food control on diets. Results: Adolescents in intervention schools, compared to control schools, had higher nutrition knowledge (mean score: 10.7 vs. 8.1, range 0-13), higher interactions with their parents (score: 8.6 vs. 8.1, range 0-10), and higher parental food control (score: 7.6 vs. 6.5, range 0-10). Higher parent-adolescent interaction (β=0.23-0.46), parents’ nutrition knowledge (β=0.28-0.73), and parental food control (β=0.23-0.41) were associated with higher dietary diversity and meal frequency. Higher parents’ education level was associated with lower junk food consumption among adolescents (OR=0.55). Interventions had largest direct effects on nutrition knowledge and parental food control and directly on adolescents’ dietary diversity and meal frequency. Exposure to food advertisements was mainly associated with junk food consumption. Conclusions: Parental roles and interactions between parents and adolescents, along with the food environment, need to be addressed to improve adolescents’ diets.